Managerial capacity among district health managers and its association with district performance: A comparative descriptive study of six districts in the Eastern Region of Ghana. - Anne Christine Stender Heerdegen; Moses Aikins; Samuel Amon; Samuel Agyei Agyemang; Kaspar Wyss (PLoS ONE, 2020)
INTRODUCTION:District health managers play a pivotal role in the delivery of basic health services in many countries, including Ghana, as they are responsible for converting inputs and resources such as, staff, supplies and equipment into effective services that are responsive to population needs. Weak management capacity among local health managers has been suggested as a major obstacle for responsive health service delivery. However, evidence on district health managers' competencies and its association with health system performance is scarce. AIM:To examine managerial capacity among district health managers and its association with health system performance in six districts in the Eastern Region of Ghana. METHODS:Fifty-nine district health managers' in six different performing districts in the Eastern Region of Ghana completed a self-administered questionnaire measuring their management competencies and skills. In addition, the participants provided information on their socio-demographic background; previous management experience and training; the extent of available management support systems, and the dynamics within their district health management teams. A non-parametric one-way analysis was applied to test the association between management capacity and district performance, which was measured by 17 health indicators. RESULTS:Shortcomings within different aspects of district management were identified, however there were no significant differences observed in the availability of support systems, characteristics and qualifications of district health managers across the different performing districts. Overall management capacity among district health managers were significantly higher in high performing districts compared with lower performing districts (p = 0.02). Furthermore, district health managers in better performing districts reported a higher extent of teamwork (p = 0.02), communication within their teams (p<0.01) and organizational commitment (p<0.01) compared with lower performing districts. CONCLUSION:The findings demonstrate individual and institutional capacity needs, and highlights the importance of developing management competencies and skills as well as positive team dynamics among health managers at district level.